Determinants of non-utilization of health facilities for childbirth in Papua New Guinea: Evidence from the demographic and health survey - McKenzie Maviso; Gracelyn Potjepat; Rebecca Bogarobu Emori; Paula Zebedee Aines; Carolyn Ruth Hastie (PLoS ONE, 2025)
Background Health facility-based childbirth services are essential for reducing maternal and neonatal mortality. Yet, these services remain underutilized in many low- and middle-income countries (LMICs), including Papua New Guinea (PNG), where birthing at home or in village settings continue to predominate. This study investigated the determinants of non-utilization of health facilities for childbirth among women in PNG. Methods Data from a weighted sample of 6,432 women using the 2016–2018 PNG Demographic and Health Survey (DHS) were analyzed. Descriptive statistics and multivariate logistic regression analyses were conducted to determine the factors associated with the non-utilization of health facilities for childbirth. The adjusted odds ratios (AOR) with their corresponding 95% confidence intervals (CI) were computed using the Statistical Package for Social Sciences, version 30.0. Results Overall, 58.3% (95% CI: 57.0–59.5) of women did not give birth in a health facility. Women were more likely to give birth at home or in the village if they had no formal education (AOR: 1.48; 95% CI: 1.11–2.09), lived in rural areas (AOR: 1.31; 95% CI: 1.11–1.75), were from the Southern (AOR: 1.05; 95% CI: 1.01–1.54), or Momase (AOR: 1.06; 95% CI: 1.02–1.83) regions, made their own healthcare decisions (AOR: 1.21; 95% CI: 1.10–4.14), had these decisions made by their husbands (AOR: 1.69; 95% CI: 1.13–2.63), walked to a health facility (AOR: 1.01; 95% CI: 1.00–1.67), or traveled more than 24 hours to access care (AOR: 1.02; 95% CI: 1.39–2.70), and had no antenatal care visits during pregnancy (AOR: 1.08; 95% CI: 1.04–1.51). Conclusions Over half of the women in this study did not utilize health facilities for childbirth. Demographic and health service-related factors influenced the non-utilization of facility-based childbirth, highlighting the need to scale up maternal health services. Increasing uptake of facility-based childbirth requires coordinated system-level efforts and incentive-based interventions that promote antenatal care and skilled birth attendance, especially for rural women. Male-inclusive strategies in maternal health decision-making are critical for improving women’s access to and utilization of facility-based childbirth services.